Survival strategies of Zimbabwean migrants in Johannesburg - Hungwe, Chipo (Expert Publisher & Association for Social and Economic Development and Promotion of Catalactica, 2016)
The study analyses Zimbabwean migrants’ strategies of survival in a largely xenophobic environment. The paper argues that exclusion of Zimbabweans in the labour market and other spheres of South Africa is largely a product of attempts by South African institutions and officials to draw boundaries separating insiders from outsiders. This inevitably limits the opportunity structure of most Zimbabwean migrants, pushing them from the formal to informal sector and further underground. Zimbabwean migrants survive by mainly concealing their identity. They adopt South African languages, ways of dressing, bribe the police and some engage in friendships, relationships and marriages with locals. Migrants also engage in self-employment, crime and church activities. The study however reveals that migrants mainly use their ethnic and religious networks, which largely promotes bonding rather than bridging social capital. Such social capital may not really help them to be integrated into the local South African community. This study is based on qualitative research conducted among Zimbabweans in the Kempton and Tembisa areas of Johannesburg, South Africa in 2012.